Excess deaths in England and Wales during the first year of COVID-19 - Ioannis Laliotis; Charitini Stavropoulou; Greg Ceely; Georgia Brett; Rachel Rushton (Global Labor Organization (GLO), 2022)
Using officially registered weekly death data, we estimate a baseline count of excess deaths during 2020 in England and Wales. We break down this number by region, age, gender, place, and cause of death. Our results suggest that there were 82,428 excess deaths in 2020 after the pandemic onset. Almost 90% of these excess deaths were due to COVID-19, suggesting that non-COVID-19 excess mortality may have been slightly higher that what has been previously estimated. Regarding deaths not due to COVID-19, individuals older than 45 years old who died at their homes, mainly from heart diseases and cancer, were the most affected. Supported by regional panel event estimates, our results highlight how measures to mitigate the pandemic spread and ease the pressure on healthcare service systems may adversely affect out-of-hospital mortality from other causes.
Keywords: I10; I18; J10; 330; COVID-19; Excess mortality; Lockdown